Is qualitative social research in global health fulfilling its potential?: a systematic evidence mapping of research on point-of-care testing in low- and middle-income contexts - Janet Perkins; Sarah Nelson; Emma Birley; Emilie Mcswiggan; Marshall Dozier; Anna McCarthy; Nadege Atkins; Eldad Agyei-Manu; Jasmin Rostron; Koichi Kameda; Ann Kelly; Clare Chandler; et al. (BMC, 2024)
Abstract Background Qualitative social research has made valuable contributions to understanding technology-based interventions in global health. However, we have little evidence of who is carrying out this research, where, how, for what purpose, or the overall scope of this body of work. To address these questions, we undertook a systematic evidence mapping of one area of technology-focused research in global health, related to the development, deployment and use of point-of-care tests (POCTs) for low-and middle-income countries (LMICs). Methods We conducted an exhaustive search to identify papers reporting on primary qualitative studies that explore the development, deployment, and use of POCTs in LMICs and screened results to identify studies meeting the inclusion criteria. Data were extracted from included studies and descriptive analyses were conducted. Results One hundred thirty-eight studies met our inclusion criteria, with numbers increasing year by year. Funding of studies was primarily credited to high income country (HIC)-based institutions (95%) and 64% of first authors were affiliated with HIC-based institutions. Study sites, in contrast, were concentrated in a small number of LMICs. Relatively few studies examined social phenomena related to POCTs that take place in HICs. Seventy-one percent of papers reported on studies conducted within the context of a trial or intervention. Eighty percent reported on studies considering POCTs for HIV and/or malaria. Studies overwhelmingly reported on POCT use (91%) within primary-level health facilities (60%) or in hospitals (30%) and explored the perspectives of the health workforce (70%). Conclusions A reflexive approach to the role, status, and contribution of qualitative and social science research is crucial to identifying the contributions it can make to the production of global health knowledge and understanding the roles technology can play in achieving global health goals. The body of qualitative social research on POCTs for LMICs is highly concentrated in scope, overwhelmingly focuses on testing in the context of a narrow number of donor-supported initiatives and is driven by HIC resources and expertise. To optimise the full potential of qualitative social research requires the promotion of open and just research ecosystems that broaden the scope of inquiry beyond established public health paradigms and build social science capacity in LMICs.